Manajemen dan Strategi Produksi Berita Televisi pada Program Warta Parlemen - Anistya, Famelia; Briandana, Rizki (Universitas Mercu Buana, 2021)
In the current era of democracy, the government is required to be more open as a public agency. Through the mass media in print and electronic form, information is intensively presented in a variety of attractive program packages. Seeing the enormous influence of the media, especially television, both government and private institutions, took the initiative to produce and broadcast news programs through institutional television stations, one of which was Parliament's TVR. The purpose of this study is to analyze the management and product strategy of the Warta Parliament program. This study uses a post-positivist paradigm and in-depth interview data collection techniques. Informants in this study were the Parliamentary TVR Team, including the Head of the Parliamentary TVR Division, the Head of the Parliamentary TVR Sub-Section, the Daily News Coordinator, and the Manuscript Editor. The results of this study show that the management and strategy of broadcasting parliamentary news is prioritized on the DPR Network (the Parliamentary TV network located in the DPR) and streaming via the website dpr.go.id and DPR now and in collaboration with TVRI, private stations (Metro TV, TVOne). , Net TV, Trans TV, Trans 7, Indosiar, RTV) to expand the reach so that people can watch Parliament TV. The Angle Selection Strategy is prioritized more on the formation of a positive image of the DPR related to the functions of the DPR, such as the Legislative Oversight Function and the Budgeting Function. The Parliamentary News Packaging Strategy is made in a 2-minute news package including Bumper, VO, sound bites from speakers including Closing